GAYA BAHASA CERPEN I’TIRĀF RUJŪLIY DALAM ANTOLOGI CERPEN MAUTU MA’ĀLĪ WAZĪR SĀBIQAN KARYA NAWAL AL-SA’DAWI: ANALISIS STILISTIKA - Albab, Zufar Ulil (STIQ Amuntai, 2023)
This study aims to reveal the beauty of language in the short story I'tirāf Rujūliy by Nawal al-Sa'dawi using stylistics performed by Syihabuddin Qalyubi. This research is a literature research with a descriptive method and qualitative approaches. Data collection using the listen method with recording techniques, analysis using the intralingual padan method, Syihabuddin Qalyubi's stylistic theory, and research results are delivered informally. The result of this study is that the style of i'tirāf rujūliy's short story contains beauty that extends to all aspects of linguistics. At the phonological level, it is found that the use of long repetition of vowel sounds. At the morphological level is found the selection of patterned word forms fā'ala-yufā'ilu, ṣīgah mubālagah, and the transfer of forms from ism al-fāil to maṣdar and from fi'il al-muḍāri' to fi'il al-māḍī. At the syntactic level, repetition and sentence structure patterns are found that investigate the rules of origin. At the semantic level, there is the use of absorptive language and synonyms. While at the level of imagery, there is the use of majzāz and tasybīh. All the styles in I'tirāf Rujūliy's short story as a whole show Nawal al-Sa'dawa's ideas about feminism, especially rejecting the cultural constructs made by patriarchy.